EXPERIENCES OF EXCLUSIVE BREASTFEEDING AMONG EMPLOYED MOTHERS AT PT. HEINZ ABC IN THE YEAR 2023 - Cahyaningsih, Intan; Fatwa, Dyah Mayasari (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2024)
Background: One contributing factor to the failure of breastfeeding is the rising prevalence of mothers engaged in full-time employment, exemplified by occupations like factory work. This phenomenon is attributed to various impediments, including restricted intervals for rest, inadequacy of workplace amenities and provisions, and the presence of fatigue. Objective: To comprehensively understand the breastfeeding endeavors of mothers employed at PT Heinz ABC factory, delving into their experiences is imperative. Methods: Qualitative The research employed a generic qualitative research approach, utilizing purposive sampling as the sampling technique. The research involved nine informants who were mothers employed in factories and had children aged between 7-24 months. Data collection was conducted through online in-depth interviews conducted via WhatsApp voice calls. The researchers also employed supportive instruments, specifically interview guides that had undergone pilot interviews beforehand. The data analysis was conducted through thematic analysis. Results: This research is segmented into three themes, namely knowledge, self-efficacy, and barriers. Conclusion: The prevalence of breastfeeding practices among mothers employed in factories remains low. This can be attributed to obstacles hindering the sustained implementation of exclusive breastfeeding, including inadequacies in workplace facilities, restricted rest intervals, psychological pressure, and low self-efficacy.